Construction and Evidence of Validity of the Positive Discipline Parenting Skills Scale - Soares, Laura Costa Mattos (2022)
This article presents the construction and evidence of validity of an instrument for measuring parenting skills based on Positive Discipline, an approach that helps parents and caregivers teach life skills to their children. The items were constructed based on a theoretical review of parenting styles, Schema Therapy and Positive Discipline and were subsequently evaluated by five expert judges and five individuals from the target audience. Following these evaluations, eight of the items were excluded and others were changed, leading to the pilot version of the Positive Discipline Parenting Skills Scale (Escala de Habilidades Parentais em Disciplina Positiva – EHPDP), represented by 28 items. Data were collected from a sample of 281 mothers with children aged 4-12 years. Exploratory factor analysis revealed a structure of 16 items divided into three factors. Cronbach’s alpha and composite reliability indicated adequate internal consistency for the instrument. Pearson’s correlation revealed evidence of convergent and discriminant validity with the validated Brazilian versions of the Parenting Styles and Dimensions Questionnaire and the Depression, Anxiety and Stress Scale. The results indicate that the EHPDP is a valid and reliable instrument to measure Positive Discipline parenting skills.